Therapeutic study of hyperbaric oxygen on heme oxygenase-1 (HO-1) in patients with acute carbon monoxide poisoning and myocardial injury: hyperbaric oxygen on heme oxygenase-1 (HO-1) in patients - Wang, Keyu; Kong, Weiwei (Cellular and Molecular Biology, 2022)
Carbon monoxide (CO) poisoning causes myocardial injury, which is attenuated by hyperbaric oxygen therapy (HBOT). During CO poisoning, the body increases anti-inflammatory proteins, including heme oxygenase-1 (HO-1), in response to oxidative stress. Considering the myocardial injury resulting from CO poisoning and the lack of sufficient information about the effect of HBOT on HO-1, the present study evaluated the effect of hyperbaric oxygen therapy on heme oxygenase-1 (HO-1) in patients with acute carbon monoxide poisoning and myocardial injury. In this regard, in a before-after Quasi-Experimental study, 20 patients with carbon monoxide poisoning and myocardial injury were studied. All patients underwent 40 daily hyperbaric oxygen therapy sessions for 90 minutes at a pressure of 2.4 ATA. Also, 20 healthy individuals, as a control group, were participated. To evaluate and compare the mRNA level of the HO-1 gene, the Real-time PCR technique was used. Paired t-test was used to compare the two indices of 6min walking distance and pulmonary arterial pressure (PAP) before and after the intervention. The results showed that the difference during 12 weeks was 8.65 ± 4.91 for PAP, and this reduction in pressure was statistically significant (P = 0.0092). The distance traveled increased by 28 ± 10.88 m in 6 minutes at the end of the study (P = 0.0084). Regarding the expression level of HO-1, the results showed that the expression level in the intervention group before the test had a significant increase compared to the control group (p = 0.0004). However, after hyperbaric oxygen therapy, the expression of this gene decreased significantly, and there was no statistically significant difference with the control group (p = 0.062). Overall, the results showed that HBOT significantly decreased HO-1 gene expression in CO poisoning and myocardial injury patients. It indicates the importance of HBOT in the treatment and compensation of cardiac tissue damage caused by CO poisoning.